2022
DOI: 10.3389/fonc.2022.912505
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor mutations and brain metastases in non-small cell lung cancer

Abstract: Studies have revealed that non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations has a high incidence of brain metastases (BMs). However, the association between EGFR mutations and BMs remains unknown. This review summarizes detailed information about the incidence of BMs, clinical and imaging characteristics of BMs, brain surveillance strategies, influence of treatments on BMs, prognosis after BMs, and differences in EGFR mutations between paired primary tumors and BMs in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Besides, the highly aggressive micropapillary subtype in adenocarcinoma with strong proliferation and migration ability was found to be associated with an increased BM risk ( 19 , 20 ). Recently, positive EGFR mutation in NSCLC patients was reported to have an impact on BM incidence in several studies ( 21 - 23 ). We also performed subgroup analysis in adenocarcinoma patients with known EGFR mutation status in our study and similar results were found.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the highly aggressive micropapillary subtype in adenocarcinoma with strong proliferation and migration ability was found to be associated with an increased BM risk ( 19 , 20 ). Recently, positive EGFR mutation in NSCLC patients was reported to have an impact on BM incidence in several studies ( 21 - 23 ). We also performed subgroup analysis in adenocarcinoma patients with known EGFR mutation status in our study and similar results were found.…”
Section: Discussionmentioning
confidence: 99%
“…Several issues need to be clarified regarding the TME and immunotherapy in NSCLC. For example, several reports showed that mRNA vaccine could be applied for cancer treatment via regulation of TME ( Zhong et al, 2021 ; Zhao W. et al, 2022 ; Huang et al, 2022 ). Proteomics, genomics, and metabolomics might be good approaches to explore the mechanism of gene mutation-driven lung cancer and TME ( Zhou et al, 2019 ; Bourbonne et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases (BM) are diagnosed in approximately 25% of all patients with a first diagnosis of metastatic EGFR-mutated ( EGFR m + ) NSCLC, and this can rise to more than 50% during the course of the disease. 1 , 2 , 3 Symptomatic BM are associated with a decrease in quality of life, and patients with BM have a worse prognosis compared with those without. 4 The percentage of patients diagnosed with having asymptomatic BM is increasing as baseline screening for (asymptomatic) BM in stages II to IV NSCLC is advised in the European Society of Medical Oncology and the National Comprehensive Cancer Network guidelines.…”
Section: Introductionmentioning
confidence: 99%